Microbial colonization of gypsum: from the fossil record to the present day - Jehlička, Jan; Oren, Aharon; Vítek, Petr; Wierzchos, Jacek (Frontiers in Microbiology, 2024)
Microorganisms inhabiting gypsum have been observed in environments that differ greatly in water availability. Gypsum colonized by microorganisms, including cyanobacteria, eukaryotic algae, and diverse heterotrophic communities, occurs in hot, arid or even hyperarid environments, in cold environments of the Antarctic and Arctic zones, and in saline and hypersaline lakes and ponds where gypsum precipitates. Fossilized microbial remnants preserved in gypsum were also reported. Gypsum protects the endolithic microbial communities against excessive insolation and ultraviolet radiation, while allowing photosynthetically active radiation to penetrate through the mineral substrate. Here, we review the worldwide occurrence of microbially colonized gypsum and the specific properties of gypsum related to its function as a substrate and habitat for microbial life on Earth and possibly beyond. Methods for detecting and characterizing endolithic communities and their biomarkers in gypsum are discussed, including microscopic, spectroscopic, chemical, and molecular biological techniques. The distribution of different microorganisms and their survival within gypsum crystals under different environmental conditions are described. Finally, we discuss gypsum deposits as possible targets for the search for microbial life or its remnants beyond Earth, especially on Mars, where sulfate-rich deposits occur, and propose strategies to detect them during space exploration missions.